Unpacking policy gridlocks in Africa's development: An evolving agenda. (1st September 2018) - Mugwagwa, Julius; Banda, Geoffrey; Bolo, Maurice; Kilonzo, Susan; Mavhunga, Clapperton; Mjimba, Vuyo; Muza, Olivia; Teka, Zeferino
Policies are not an end in themselves, but deliberate systems of principles to guide decisions and achievement of rational outcomes. Many factors inherent in or transcending policy processes have dramatic consequences for how policies are interpreted and applied. In this article, we deploy the concept of 'policy gridlocks' to better understand factors that facilitate or hinder implementation of single or multiple policies in different African policy arenas. We argue that minimizing or ameliorating 'policy gridlocks' requires stakeholders to quantify and more directly feel the cost of their decisions and actions, while scholars must continue to search for institutional means to prevent gridlocks, including broadening the array of conceptual and analytical tools for understanding policy processes. We conclude that limits in financial resources, technical expertise and legislative capacity are the more powerful drivers of policy formulation, implementation and revision gridlocks that need to be addressed, than fragmentation of stakeholder interests.